Second language writing anxiety: cause or effect? - Mat Daud, Nor Shidrah; Mat Daud, Nuraihan; Abu Kassim , Noor Lide (Malaysian English Language Association (MELTA), 2005)
Writing is a demanding activity especially for learners of a second / foreign language and yet it is a skill that they have to master in order to do well in content courses especially at the tertiary level of education. Studies have shown that students’ writing performance is related to anxiety. What is uncertain is whether anxiety is the cause or the consequence of poor writing performance. This study seeks to find how anxiety is related to performance using the deficit hypothesis as its guiding principle. The findings show that the subjects in this study suffered anxiety as a result of their lack of writing skills, and that the better students experienced less anxiety than the weaker ones.